Silicone Brake Fluids: One-Year Field Test. - Conley,James H.; Jamison,Robert; Jordan,Charles B. (1975)
A study is being conducted to evaluate the performance of silicone brake fluids in military vehicles operating under various climatic conditions. These fluids are being field tested in vehicles operating at the Tropic Test Center (TTC), Panama Canal Zone; Yuma Proving Ground (YPG), Arizona; and Arctic Test Center (ATC), Fort Greeley, Alaska. After one year's operation in Panama, all brake systems using the silicone performed far superior to the conventional fluid. At YPG, no significant differences were noted. In Alaska, the test was discontinued on two of the three silicones because of possible crystallization at temperatures below -50F. The third fluid performed satisfactorily throughout the test period. Additional tests using two fluids with improved low-temperature properties were initiated. The tests are continuing with inspections planned after 2 years' operation.